An Amine–Borane System Featuring Room‐Temperature Dehydrogenation and Regeneration. (12th April 2021) - Zhang, Guojin; Morrison, Daniel; Bao, Guochen; Yu, Haibo; Yoon, Chang Won; Song, Taekyong; Lee, Jihye; Ung, Alison T.; Huang, Zhenguo
Abstract: Amine–borane complexes have been extensively studied as hydrogen storage materials. Herein, we report a new amine–borane system featuring a reversible dehydrogenation and regeneration at room temperature. In addition to high purity H2, the reaction between ethylenediamine bisborane (EDAB) and ethylenediamine (ED) leads to unique boron–carbon–nitrogen 5‐membered rings in the dehydrogenation product where one boron is tricoordinated by three nitrogen atoms. Owing to the unique cyclic structure, the dehydrogenation product can be efficiently converted back to EDAB by NaBH4 and H2 O at room temperature. This finding could lead to the discovery of new amine boranes with potential usage as hydrogen storage materials. Abstract : An amine–borane system has been discovered to deliver a reversible dehydrogenation/regeneration at room temperature. It provides a new way for hydrogen storage under mild conditions.